2022
DOI: 10.3389/fsurg.2021.816763
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Multidisciplinary Team Co-Management Program for Elderly Patients With Intertrochanteric Fractures: A Retrospective Study

Abstract: BackgroundIntertrochanteric fractures increased quickly in past decades owing to the increasing number of aging population. Recently, geriatric co-management was rapidly emerging as a favored clinical care model for older patients with hip fractures. The purpose of this study was to assess the efficacy of a multidisciplinary team (MDT) co-management program in elderly patients with intertrochanteric fractures.MethodsIn this retrospective study, patients were divided into MDT group and traditional orthopedic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
(42 reference statements)
2
2
0
1
Order By: Relevance
“…Previous work concurs with our finding of no clear benefit of MFT care on short-term survival [ 11 , 14 , 15 , 25 ]. This may reflect that the primary risk factors for mortality soon after hip fracture surgery are age, sex, and preoperative complications [ 9 , 26 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Previous work concurs with our finding of no clear benefit of MFT care on short-term survival [ 11 , 14 , 15 , 25 ]. This may reflect that the primary risk factors for mortality soon after hip fracture surgery are age, sex, and preoperative complications [ 9 , 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our results support previous studies that found MFT care to shorten hospitalization and accelerate recovery among geriatric patients covering a wide age range from 60 years and older who underwent.hip fracture surgery [ 11 18 ]. At least in the present study, the advantages of MFT care are likely due in part to clinicians’ efforts to perform surgery within 72 h after admission.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, no significant differences were observed in postoperative mortality within 1 year between TXA group and control group. The main reasons of high mortality rate in the elderly patients with intertrochanteric fractures are various complications such as respiratory infection, lower extremity deep vein thrombosis, and pressure ulcers ( Fan et al, 2021 ). Our study demonstrated that the administration of TXA did not increase the risk of the complications.…”
Section: Discussionmentioning
confidence: 99%
“…Si el manejo definitivo propuesto es la cirugía, el paciente se encuentra estable y está de acuerdo con el manejo quirúrgico y los exámenes se encuentran en los rangos aceptados, entonces debe procederse con la cirugía lo antes posible, dentro de las primeras 24-48 horas (5,44,46). Solicitud de exámenes.…”
Section: Indicacionesunclassified